The discourse of beauty standard in fashion advertising language on Facebook: The C&A brand and its relationship with female beauty in Brazil and Portugal - Oliveira, H.; Lapa, T. (8th European Communication Conference - https://www.ecrea2020braga.eu/8th-ecrea-conference-6-9-september-2021/, 2021)
This paper comprehends a study that compares and analyzes the manner forms of feminine beauty are approached in the spring / summer 2018 advertisement campaigns on Facebook pages of the C&A clothing retailer in Brazil and Portugal. Over the years, changes in paradigms and stereotypes related to female beauty standards have been unfolding. The influence of feminism that challenges the mediatization of stereotyped representations of femininity or “contingents of female reality” (Martins, 2016: 1), the appreciation of identity and forms of personal expression are revealing that society creates new forms to interpret, relate and express yourself constantly. The representation of “body and beauty” (Kuipers, 2009) and also the recognition that the female audiences go far beyond cisgender women (those who identify with the gender in which they were born) but also include other forms of female identities and expressions (Butler, 1993). Therefore, the main purpose of the present paper is the understanding of how the brand C&A approached female beauty to female audiences (defined as people who identify themselves as female) in both countries. It is argued that present day fashion brands and aesthetic products advertisement campaigns are influenced by social disputes concerning the “media aesthetic and fashionable aesthetic standard of female beauty” (Anzai, 2000; Martins, 2016). Therefore, it is relevant to examine if the feminist challenge to traditional forms of representation of what is “feminine beauty” is enabling change, or not, in the ways brands deal with and relate to their female audiences. This is an exploratory study that followed a mixed methods methodological approach, divided in two stages. First, a semiotic analysis of the image content of the spring / summer 2018 campaigns of the brand C&A Brazil and Portugal on Facebook, that included the categorization of elements and comparison between campaigns. Second, an online survey, where data was collected on the physical characteristics of the respondents in order to establish a comparative relation with the perceived physical characteristics of the professional female models in the campaign images. Next, these characteristics were compared between the female population resident in Brazil and Portugal, using as basis the categories discussed in the first stage of this methodology. In addition, responses concerning the interviewees' representations and attitudes towards the images of the analyzed campaigns were also collected. The results of this paper show that the brand subtly sought to represent different forms of feminine beauty, albeit in conservative parameters. It also reveals that interviewed women in both countries, for the most part, have a critical reaction towards the analyzed campaigns, stating, in many cases, that the portrait of feminine beauty in the images of the campaigns are not adequate.